The relationship between depressive mood and non-suicidal self-injury among secondary vocational school students: the moderating role of borderline personality disorder tendencies - Lu, Zhaoyuan; Chen, Mo; Yan, Shu; Deng, Weixi; Wu, Taimin; Liu, Lianzhong; Zhou, Yang (Frontiers in Psychiatry, 2023)
Background Non-suicidal self-injury (NSSI) has become an important public health issue of global concern, often occurring in adolescents, and depressive mood is closely related to NSSI. In addition, NSSI is considered a symptom of borderline personality disorder. It has been found that adolescents in secondary vocational schools are more vulnerable to behavior and emotional disorders than those in general high schools. This study investigated the risk factors associated with NSSI affecting secondary vocational school students and analyzed the role of borderline personality disorder tendencies in promoting the occurrence of NSSI among students with depressive moods. Methods A total of 1,848 Chinese secondary vocational students completed a self-report questionnaire. The homemade NSSI behavior questionnaire, Patient Health Questionnaire-9 and Personality Diagnostic Questionnaire-4 were used in this survey. Binary logistic regression and PROCESS software analysis were used to explore the influencing factors associated with NSSI and to test for moderating effects. Results Female (OR = 3.412, 95% CI 2.301–5.060), drinking history (OR = 2.007, 95% CI 1.383–2.911), history of suicidal death exposure (OR = 3.161, 95% CI 1.999–4.999), depressive mood (OR = 2.436, 95% CI 1.668–3.558) and borderline personality disorder tendencies (OR = 2.558, 95% CI = 1.764–3.711) were independent risk factors for NSSI. Borderline personality disorder tendencies (B = 0.047, p = 0.000) moderated the relationship between depressive mood and NSSI. The stronger the borderline personality tendencies, the more NSSI behavior occurred when they were depressive. Conclusions Borderline personality disorder tendencies in secondary vocational school adolescents significantly enhance the association of depressive mood with NSSI. There is a moderating role for borderline personality disorder tendencies in depressive mood and NSSI.